Aid for trade : cool aid or kool-aid? - Laird, Sam (UN New YorkUS, 2007)
Defines Aid for Trade and discusses its role and place within multilateral institutions during recent years. Examines the need for aid for trade, reviews recent development in WTO negotiations and discusses private sector issues.